Electrosprayed Collagen/Gentamicin nanoparticles coated microneedle patches for skin treatment - ŞENGÖR, MUSTAFA; GÜNDÜZ, OĞUZHAN (ELSEVIER, 2021)
In this study, biocompatible microneedle patches were fabricated with three dimensional stereolithography (3D SLA) printer and coated with Gentamicin (GEN)-loaded Collagen (COL) nanoparticles fabricated with the electrospray method. The SEM results of the microneedles and COL/GEN nanoparticles coated microneedles showed that the nanosized microneedles were fabricated successfully, and these microneedles were coated with 1% COL/ GEN solutions homogeneously. The release profiles of the GEN from the 1% COL/GEN nanoparticles coated microneedles reported that the drug was completely released within 540 min.
Keywords: Collagen type I; Electrospraying; Gentamicin; Microneedle; Nanoparticles; 3D printing; RELEASE